Existence of Solutions for a Periodic Boundary Value Problem via Generalized Weakly Contractions - Sirous Moradi; Erdal Karapınar; Hassen Aydi (Abstract and Applied Analysis)
We discuss the existence of solutions for a periodic boundary value problem and for some polynomials. For this purpose, we present some fixed point theorems for weakly and generalized weakly contractive mappings in the setting of partially ordered complete metric spaces.